Clinical and pathological characteristics of patients with colorectal cancer under age stratification - Liu, Zhuoran; Kong, Wei; Lin, Yingmin; Yin, Tengfei; Wang, Min (Frontiers in Oncology, 2026)
BackgroundThe incidence of early-onset colorectal cancer is increasing. The rate of early diagnosis and screening is low, and the prognosis is poor. This study aims to compare the clinical and pathological characteristics of colorectal cancer patients under age stratification, so as to improve the awareness of prevention in different populations and provide the basis for treatment strategies.MethodsThis retrospective cross-sectional study included patients who underwent electronic colonoscopy and were diagnosed with colorectal cancer by pathology in Qilu Hospital of Shandong University from July 2017 to June 2020. Their clinical and pathological data were statistically analyzed according to <40 years, 40–50 years and >50 years groups.Results850 patients were included (40 <40 years, 108 40–50 years, and 702 >50 years). The proportions of comorbidities (7.5% vs 26.8% vs 55.4%, p=0.006) and medical history were higher (12.5% vs 11.1% vs 17.1%, p=0.163) in the >50 years group; the proportion of family history was higher in the <40 years group (10.0% vs 9.3% vs 3.8%, p=0.015). All patients in the age group under 40 years had symptoms (100% vs 96.3% vs 93.4%, p=0.161), while some patients in the other two groups did not. The incidence of left-sided colon was higher in the <40 years group (37.5% vs 25.0% vs 23.1%, p=0.392); the incidence of right-sided colon was higher in the 40–50 and >50 years group (10.0% vs 25.9% vs 21.9%, p=0.392). Low-grade (7.5% vs 5.6% vs 5.4%, p=0.057), mucinous adenocarcinoma (15.0% vs 9.3% vs 3.6%, p=0.002) and signet ring cell carcinoma (5.0% vs 0.9% vs 0.3%, p=0.002) were more common in the <40 years group. Late-stage tumors were more common in the <50 years group (65.0% vs 51.9% vs 46.6%, p<0.01); early-stage tumors were more common in the >50 years group (35.0% vs 48.2% vs 53.4%, p<0.01).ConclusionThere are more family history in early-onset colorectal cancer patients, with various symptoms, mucinous adenocarcinoma and signet ring cell carcinoma, poor tumor differentiation and late stage. Young adults with symptoms should undergo colonoscopy actively. For patients <40 years, genetic testing should be performed.